AN ANALYSIS ON SYMBOLISM USED IN REBA TRADITIONAT GURU SINA - Wilibrodus Kumi; Siane Herawati (JURNAL ILMIAH BAHASA DAN SASTRA, 2016)
Reba Tradition is part of Guru Sina’s tradition and an event which is interested to participate, many kinds of symbols used on it. Reba Tradition is not separated from language. By using language, the researcher can express our thought, idea, emotion, and feeling. Because language is an important aspect of human life and social communication among the members of society. Therefore, the researcher has been interested in studying this problem by formulating four researcher problems such as: What is the background of Reba Tradition at Guru Sina? How are the implementation process of Reba tradition at Guru Sina? What are symbols and meaning of those symbols are used in Reba tradition at Guru Sina?and What are functions Reba tradition for people at Guru Sina? This study has two significances of the study, theoretically and practically. Theoretically, the result of this study will give the description about the symbols are used in Reba tradition. Practically, the researcher hopes this research is useful to enrich Reba tradition and as additional knowledge for people or student both from Ngada or others. The research of this thesis is descriptive qualitative research. It is intended to describe about the symbols, and also the symbols meaning used in Reba tradition. Key words: and